Contemporary approaches to upper respiratory tract infections - Chonmaitree, Tasnee; Patel, Janak A. (Future Medicine Ltd, 2016)
Designed with clinicians in mind, this book aims to help them better understand the pathogenesis of disease as well as develop clinical management decisions for patients suffering from these conditions.